Association between atherogenic dyslipidemia and muscle quality defined by myosteatosis - Kim, Hwi Seung; Cho, Yun Kyung; Kim, Myung Jin; Kim, Eun Hee; Lee, Min Jung; Lee, Woo Je; Kim, Hong-Kyu; Jung, Chang Hee (Frontiers in Endocrinology, 2024)
Background: Myosteatosis, ectopic fat accumulation in skeletal muscle, is a crucial component of sarcopenia, linked to various cardiometabolic diseases. This study aimed to analyze the association between dyslipidemia and myosteatosis using abdominal computed tomography (CT) in a large population. Methods: This study included 11,823 patients not taking lipid-lowering medications with abdominal CT taken between 2012 and 2013. Total abdominal muscle area (TAMA), measured at the L3 level, was segmented into skeletal muscle area (SMA) and intramuscular adipose tissue. SMA was further classified into normal attenuation muscle area (NAMA: good quality muscle) and low attenuation muscle area (poor quality muscle). NAMA divided by TAMA (NAMA/TAMA) represents good quality muscle. Atherosclerotic dyslipidemia was defined as high-density lipoprotein cholesterol (HDL-C) less than 40 mg/dL in men and 50 mg/dL in women, low-density lipoprotein cholesterol (LDL-C) greater than 160 mg/dL, triglycerides (TG) greater than 150 mg/dL, small dense LDL-C (sdLDL-C) greater than 50.0 mg/dL, or apolipoprotein B/A1 (apoB/A1) greater than 0.08.The adjusted odds ratios (ORs) of dyslipidemia according to the HDL-C and sdLDL definitions were greater in both sexes in the lower quartiles (Q1~3) of NAMA/TAMA compared with Q4. As per other definitions, the ORs were significantly increased in only women for LDL-C and only men for TG and ApoB/A1. In men, all lipid parameters were significantly associated with NAMA/TAMA, while TG and ApoB/A1 did not show significant association in women.Myosteatosis measured in abdominal CT was significantly associated with a higher risk of dyslipidemia. Myosteatosis may be an important risk factor for dyslipidemia and ensuing cardiometabolic diseases.